1999
DOI: 10.1055/s-2007-978777
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pramlintide (Amylin Analogue) Treatment on Bone Metabolism and Bone Density in Patients with Type 1 Diabetes Mellitus

Abstract: Amylin is a 37-amino-acid peptide related to CGRP and calcitonin. It is co-secreted with insulin from pancreatic beta-cells. Amylin is deficient with type 1 diabetes mellitus. To study the in vivo effects of amylin in humans, diabetic patients are an adequate model of chronic amylin deficiency. We investigated the effect of a 12 months pramlintide therapy (amylin analogue) on bone metabolism in patients with type 1 diabetes mellitus. 23 patients with type 1 diabetes mellitus (age 45.2 +/- 10.3 years, duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…There was no statistically significant change in BMD or markers of bone metabolism after 1 year. The subjects did not have osteopenia at baseline, and therefore the impact of pramlintide on bone metabolism in patients with T1DM and osteopenia is unclear (137).…”
Section: Results From Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no statistically significant change in BMD or markers of bone metabolism after 1 year. The subjects did not have osteopenia at baseline, and therefore the impact of pramlintide on bone metabolism in patients with T1DM and osteopenia is unclear (137).…”
Section: Results From Clinical Trialsmentioning
confidence: 99%
“…The impact of pramlintide on bone metabolism has not been extensively studied. Borm et al (137) conducted a small clinical trial in 23 patients (13 males and 10 females) with T1DM (age, 42.2 Ϯ 10.3 y; duration of diabetes, 20.7 Ϯ 9.8 y) that investigated the effect of 12 months of treatment with pramlintide on bone metabolism. BMD measurement of the lumbar spine by dual-energy x-ray absorptiometry and biochemical markers of bone metabolism, including calcium, PTH, osteocalcin, and urinary pyridinium crosslinks, were obtained at baseline and after 1 year of treatment with pramlintide.…”
Section: Results From Clinical Trialsmentioning
confidence: 99%
“…However, only one study has directly examined the skeletal effects of pramlintide therapy in humans. In a study of 23 non‐osteoporotic T1D patients (mean age ~45 years; mean duration of T1D ~21 years), 12 months of treatment with pramlintide, as four injections per day, did not impart a significant change in BMD, or in bone biomarkers (calcium, PTH, osteocalcin, pyridinium cross‐links) after 1 year . However, because these subjects were not osteoporotic at baseline, the implication of these findings may be limited; moreover, they do not provide any evidence of the impact of pramlintide on fracture risk, specifically.…”
Section: Drugs and Bonementioning
confidence: 93%
“…In addition, the study found that women with anorexia nervosa had significantly lower levels of fasting amylin, suggesting that amylin could be one of the mechanisms underlying bone loss in anorexia nervosa (85). In another study, a group of patients with type 1 diabetes were treated with pramlintide (amylin analog) for 12 months (86). Although these patients were expected to benefit from the therapy due to the chronic amylin deficiency associated with diabetes, no change in BMD or biochemical markers of bone metabolism was observed following the treatment.…”
Section: Beta-pancreatic Hormonesmentioning
confidence: 99%